Retrospective Study of Cystic Echinococcosis (CE) Based on Hospital Record from Five Major Metropolitan Cities of Pakistan - Muqaddas, Hira; Arshad, Muhammad; Ahmed, Haroon; Mehmood, Naunain; Khan, Aisha; Simsek, Sami (Springer Int Publ Ag, 2019)
Background Human cystic echinococcosis (CE) is an important zoonotic parasitic disease. It is one of the NTDs having strong roots in Pakistan. There are limited studies on the prevalence of CE in Pakistan. Method A retrospective study was conducted to determine the geographical distribution of human CE in Punjab (Lahore, Multan, and Faisalabad) and Sindh (Karachi and Hyderabad) provinces of Pakistan. Clinical records of infected patients from nine major hospitals were retrieved from 2008 to 2018. Results A total of 188 surgically confirmed cases were included from selected hospitals during the study period, which showed the annual frequency of 18.8 cases/year. The number of reported cases was higher in Sindh province (67.55%) compared to Punjab (32.45%). Total number of CE cases/city was higher in Karachi (47.34%) compared to Hyderabad city (20.21%), while in Punjab province, this frequency was higher in Lahore (25%) followed by Multan (5.32%) and Faisalabad (2.13%). Out of total 188 patients, 73 (38.83%) were males and 115 (61.7%) were females. In surveyed hospitals, high burden of infection was reported in young adults (21-30 years; 29.79%) followed by 21.81% and 17.02% in 31-40 and 41-50 age groups, respectively. Data retrieved from the hospital record of diagnosed cases of CE showed liver (36.17%, n = 68) as the most affected organ followed by lungs (26.06%, n = 49). In this survey, some unusual sites of cyst formation were also observed. Conclusion Current study is a step forward towards filling the gap of knowledge for prevalence and regional distribution of hydatidosis in Pakistan reporting the CE cases in humans for the first time in Multan and Faisalabad.
Keywords: Cystic echinococcosis; Geographical distribution; Sindh; Punjab; Pakistan